Regulatory pluralism: positing priority actions in waste and recycling management. Issue 4 (1st October 2020) - Lodhia, Sumit; Martin, Nigel; Rice, John
ABSTRACT: The annual management of 67 million tonnes of waste and recycling streams poses significant environmental pollution and regulatory challenges to Australian governments. While the Australian government has carriage of waste and recycling policy and coordination, operational aspects rest with state-territory and local governments. This research examined stakeholder perspectives and, while lacking in individual and community client data inputs, exposed regulatory limitations, waste and recycling problems and issues, and forward trajectories for waste policies and programs. Regulatory pluralism theory served as the study's lens, showing that the rapid rise in waste production and reduced waste transfers to China will require a composite of improved waste regulations, landfill and waste handling management practices; additional recycling behaviour modification incentives; and domestic and international waste and recyclate markets development. In addition, the analysis highlighted the important leadership role for the federal tier of waste governance in product stewardship reform, and the advancement of waste and recycling infrastructure development under new national cabinet and federal reform arrangements. Importantly, from the theory perspective, the research built into the cumulative tradition of pluralistic regulatory systems development.